Respuesta :
Answer:
Step 1: 14x − 21 = 1; Step 2: 14x = 22
Explanation:
7(2x−3)=1
Step 1: Simplify both sides of the equation
7(2x−3)=1
(7)(2x)+(7)(−3)=1(Distribute)
14x+−21=1
14x−21=1
Step 2: Add 21 to both sides
14x−21+21=1+21
14x=22
Step 3: Divide both sides by 14
14x / 14 = 22 / 14
x = 22 / 14: x = 11/7
Answer:
The last option.
Step-by-step explanation:
When distributed, 7 times 2x becomes 14x and 7 times -3 is -21.
Once you add -21 to both sides, 14x is left alone on one side while 22 is on the other